(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
The exterior square is a homological functor originated in the homotopy theory, while Bieberbach groups with symmetric point group are torsion free crystallographic groups. In this paper, the generalization of the exterior square of a Bieberbach group with symmetric point group is constructed up to finite dimension.